Modelul şi oglinda. E. Lovinescu „par lui même” - Antonio Patraș (Revista de Istorie și Teorie Literară)
E. Lovinescu received his due acknowledgment as the main representative of the Romanian inter-bellum culture. His aesthetic criticism pleaded for the necessary modernization of our literature, by means of imitating salient Western models. Although his image in posterity represents a conglomerate of mere clichés, the critic proves to be, under close-scrutiny, a complex theorist (even though, quite often, a rather contradictory one). He aimed to assess literature from a psycho[1]sociological point of view and to articulate a consistent theory on personality, with a particular focus on those processes that recur during our inner development. The branded ‘theory of forms without content’ served Lovinescu as a marvelous hypothesis to assess the emergence of Romanian modern civilization. Therefore, the critic’s coherent program hinted at the modernization of Romanian literature, centered upon theories such as ‘the primate of aesthetical value’ and the urge for ‘synchronization’. In any case, the harsh aestheticism proceeded rather uniformly, as a unifying agent, neglecting all virtual exceptions.